2011
DOI: 10.1103/physrevb.83.024418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostrictive Néel ordering of the spin-52ladder compound BaMn2O

Abstract: The crystal structure and the magnetism of BaMn2O3 have been studied by thermodynamic and by diffraction techniques using large single crystals and powders. BaMn2O3 is a realization of a S = 5/2 spin ladder as the magnetic interaction is dominant along 180• Mn-O-Mn bonds forming the legs and the rungs of a ladder. The temperature dependence of the magnetic susceptibility exhibits well-defined maxima for all directions proving the low-dimensional magnetic character in BaMn2O3. The susceptibility and powder neut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…On the basis of local density approximation (LDA) calculations, Han et al suggested ferromagnetic spin interactions along the ladders, [6] but this has to be confirmed by neutron diffraction. However, a symmetry breaking was the reason for long-range magnetic ordering in BaMn 2 O 3 [4] and a small staggering between the ladders in α-BaFe 2 Se 3 is observed on magnetic ordering (i.e., there is a strong magnetoelastic coupling even without intrinsic geometric frustration). [14] Moreover, extra phonons appear in the Raman data below 240 K in BaFe 2 Se 2 O.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…On the basis of local density approximation (LDA) calculations, Han et al suggested ferromagnetic spin interactions along the ladders, [6] but this has to be confirmed by neutron diffraction. However, a symmetry breaking was the reason for long-range magnetic ordering in BaMn 2 O 3 [4] and a small staggering between the ladders in α-BaFe 2 Se 3 is observed on magnetic ordering (i.e., there is a strong magnetoelastic coupling even without intrinsic geometric frustration). [14] Moreover, extra phonons appear in the Raman data below 240 K in BaFe 2 Se 2 O.…”
Section: Resultsmentioning
confidence: 96%
“…However, the low-temperature spin ordering could be different in the two modifications. In other ladder compounds (e.g., BaMn 2 O 3 ), [4] the low-dimensional magnetic behavior is clearly due to the geometric frustration between the ladders, marked for the title compound with dashed lines in Figure 2b. Hence, the crystallographic mirror plane with its normal parallel to the a axis might play an important role in the magnetic properties of both BaFe 2 S 2 O and BaFe 2 Se 2 O, as both dashed lines have to result in two equally strong antiferromagnetic couplings between the ladders.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, the onset of incommensurate harmonic order at T N has no magnetoelastic impact on the b lattice parameter. In most magnetoelastic materials [26][27][28][29][30] , anomalies in the strain are coupled to the order parameter, typically the (staggered) magnetic moment, and thus appear just at T N , while the situation in NaFe(WO 4 ) 2 is more complex. In NaFe(WO 4 ) 2 , the change in the lattice is not proportional to a power of the averaged ordered moment, |m| , but to the emergence of anharmonicity either in the incommensurate phase or in the commensurate order.…”
Section: Microscopic Measurementsmentioning
confidence: 99%
“…Firstly, the effects are rather large yielding a relative reduction of the b lattice param- eter by up to ∆b b −2.6 · 10 −4 , and, secondly, there is no magnetoelastic anomaly at the onset of magnetic ordering in zero field, which results in the incommensurate phase. In most systems with strong magnetoelastic effects one may couple the strain, , with some power of the ordered moment defined as m av = |m| [26][27][28][29][30]40 , but in NaFe(WO 4 ) 2 the intermediate incommensurate phase renders the analysis more complex. Apparently there is only a weak coupling to the incommensurate phase, while that to the commensurate order parameter is strong.…”
Section: Magnetoelastic Coupling In Nafe(wo4)2mentioning
confidence: 99%